A concise history of Salmonella spp. nomenclature - EVANGELOPOULOU, GD; BOURRIEL, A; SPYROU, V (Journal of the Hellenic Veterinary Medical Society, 2018)
The history of typing strains of the genus Salmonella is a matter, perhaps, causing anxiety to those choosing to do research with this microorganism. The nomenclature and taxonomy of microorganisms of great Public Health importance, such as Salmonella, are causing proliferation of opinions and information representing various "schools of thought". They produce a difficult to manage bulk of scientific information, eventually deterring inexperienced newcomers in this field of research. In overcoming this confusing proliferation of information, international bodies, having the responsibility of summarizing and officializing available knowledge, publish regularly "landmark decisions" on nomenclature and taxonomy. The present concise review of the history of Salmonella nomenclature aims in guiding the inexperienced researchers studying salmonellosis in animals and man toward the sources of accurate information.